Characteristics, management, and outcomes of congenital biliary dilatation in neonates and early infants: a 20‐year, single‐institution study. (21st November 2018) - Urushihara, Naoto; Fukumoto, Koji; Yamoto, Masaya; Miyake, Hiromu; Takahashi, Toshiaki; Nomura, Akiyoshi; Sekioka, Akinori; Yamada, Yutaka; Nakaya, Kengo
Abstract: Background: The aim of the present study was to investigate the characteristics, management, and outcomes of congenital biliary dilatation (CBD) in neonates and infants (<1 year old) in a single institution over the past 20 years. Methods: From 1997 to 2016, 21 patients <1 year old underwent definitive surgery for CBD. Open surgery (OS) was performed between 1997 and 2008, and laparoscopic surgery (LS) has been performed since 2009. Results: The bile duct showed cystic dilatation in all patients. Sixteen (76.2%) of the 21 patients were diagnosed prenatally, and the incidence increased with time (OS 63.6%, LS 90%). Fourteen patients (66.7%) were symptomatic before surgery, with jaundice in 11 (52.4%), acholic stool in seven (33.3%), and vomiting in three (14.3%). There were no significant differences in operation time and blood loss, but the postoperative fasting period and hospital stay were significantly shorter in the LS group ( P < 0.05). There were no intraoperative complications, but there was one postoperative early complication in one LS group patient, who had bile leakage and was treated with redo hepaticojejunostomy. Conclusion: The incidences of prenatally diagnosed and asymptomatic patients increased with time. Although longer follow‐up is needed, LS for CBD could be safely performed even in neonates and early infants. Abstract : Highlight Urushihara and colleagues set out to evaluate the characteristics, management, and outcomes of congenital biliary dilatation (CBD) in neonates and infants. The number of patients with prenatally diagnosed CBD has been increasing dramatically, which allows elective surgery before symptoms appear. Laparoscopic surgery for CBD could be safely performed even in neonates and early infants.